Bulk and Activated Carbon-Supported Tungstophosphoric Acid as Recyclable and Green Catalyst for One-Pot Synthesis of β-Acetamido Ketones and Esters - Fatemeh F. Bamoharram; Ali Ahmadpour; Majid M. Heravi; Mohammad J. Sane Charkhi (E-Journal of Chemistry)
A rapid and efficient one-pot method for the synthesis of β-acetamido ketones/esters has been developed in the presence of bulk tungstophosphoric acid and its supported forms on activated carbon as recyclable and eco-friendly catalysts under refluxing conditions. Supported tungstophosphoric acid catalysts containing the same amount of heteropoly acid yielded much higher conversion than bulk form.